(untitled) (Research, Society and Development, 2023)
The treatment of multiple pediatric mandible fractures is a challenge for the oral and maxillofacial surgeon. The decision regarding conservative treatment or surgical intervention must be based on a correct diagnostic elucidation process, adequate imaging exams and the clinical evaluation of the patient. Methodology: this work is a descriptive study, of the case report type, elaborated through anamnesis, complementary exams, as well as photographs of the patient. Objective: This work consists of demonstrating a case of a 10-year-old boy, victim of a fall from his own height in contact with a domestic animal, attended the Oral and Maxillofacial Surgery and Traumatology service of an emergency hospital with a complaint of “pain in face". A diagnosis of multiple mandible fracture involving the region of the left ramus, right parasymphysis and right ramus was made. Transcervical access was performed due to the presence of multiple affected mandibular sites, reduction and fixation of fractures, which offered a satisfactory treatment for the patient. Final considerations: Although rare, pediatric facial trauma remains a dramatic condition associated with major morbidities and predisposing sequelae. Bilateral transcervical access in pediatric patients continues to be an option of great value for specific cases: fractures with great displacement and multiple mandibular sites involved. Surgical planning and surgeon expertise are keys to correct execution.